Factors affecting sukuk market, bond market, Islamic banking and conventional banking development in selected countries - Aman, Ameenullah (2020)
The Asian crisis (1997) and the world economic crisis (2008) have taught the lesson to both developed and developing economies, that a well-developed financial system needs the inclusion of both, a developed banking system as well as developed sukuk and bond markets. Since macroeconomic and financial factors play a key role in the development of any financial market, this study investigates the macroeconomic and financial determinants of sukuk and bond markets, and Islamic and conventional banks. Unbalanced panel data is collected for sukuk market (13 countries, period 1996-2017), bond market (10 countries, period 1993-2017), Islamic banking (10 countries, period 1993-2017), and conventional banking system (12 countries, period 1993-2017). Content analysis, panel least square and fixed effect models are employed. Findings reveal Malaysia as a market leader in global sukuk markets, the United Sates leads in bond markets, Saudi Arabia holds largest Islamic banking assets, and Bahrain holds largest conventional banking assets, against respective gross domestic product, from the sample countries. Empirically, sukuk market has negative effect from economic size, economic development, exports, interest rate and stock market, and positive effect from current account and banking system. In contrast, bond market has positive effect from economic size, exports, current account, and banking system, and negative effect from economic development and interest rate. Further, economic size has positive effect on Islamic banks and negative effect on conventional banks, Islamic banks have positive effect from banking liabilities and negative effect from stock markets. Contrary, conventional banks have negative effect from banking liabilities and positive effect from stocks. The study contributes the need for the stable macroeconomic and financial environment for the smooth development of sukuk and bond markets as well as Islamic and conventional banking systems.